2015
DOI: 10.1039/c5ra13298c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast dynamics of a molecular rotor in chemical and biological nano-cavities

Abstract: Molecular rotors have become indispensable tools to monitor several important processes inchemistry and biology owing to their sensitivity towards viscosity. Despite their importance, less attention has been paid to understand the excited state properties of molecular rotors.Recently, Maroncelli and coworkers unraveled the excited state photochemistry of julolidine based molecular rotor, 9-(2-carboxy-2-cyano)vinyl julolidine (CCVJ), and claimed that CCVJ is not a simple rotor probe. Unlike other molecular roto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It was shown that such physical parameters influence molecular rotational motion,r esulting in changes to the FL quantumy ield. [86] In a rectangulart ube, when the flow patterns of CCVJ followed a parabolic profile andt he velocity of the fluid increased, the FL intensity linearly increased over ac ertain range. CCVJ exhibited similar behavior in fluidic chambers,v alidating its utility as a probe forshear stress and fluid flow.…”
Section: Microfluidicapplicationsmentioning
confidence: 97%
“…It was shown that such physical parameters influence molecular rotational motion,r esulting in changes to the FL quantumy ield. [86] In a rectangulart ube, when the flow patterns of CCVJ followed a parabolic profile andt he velocity of the fluid increased, the FL intensity linearly increased over ac ertain range. CCVJ exhibited similar behavior in fluidic chambers,v alidating its utility as a probe forshear stress and fluid flow.…”
Section: Microfluidicapplicationsmentioning
confidence: 97%
“…36 DCVJ has also been used to study different complex molecular systems, such as protein aggregates 37−40 and supramolecular assemblies. 25,30 Recently, DCVJ has been used as a turn-on fluorescence sensor in different applications related to nucleic acid. For example, Wu et al have shown that DCVJ can selectively bind to the abasic sites of DNA, resulting in large enhancement in its emission.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a variety of interesting applications of synthetic rotary molecular motors have been reported [ 43 46 ], such as in molecular transport [ 44 ] and in viscosity sensing [ 45 , 46 ]. A key requirement for such applications is that the motors are able to reach high rotational frequencies under ambient conditions [ 27 , 47 ].…”
Section: Introductionmentioning
confidence: 99%